The phytotoxic effects of palm oil dry solids on plant growth - Othman, Radziah; Hashim, Azizah; Abdul Rahman, Zaharah (Universiti Putra Malaysia Press, 1997)
Glasshouse and laboratory experiments were conducted to evaluate the phytotoxicity of palm oil dry solids (PODS) on growth of vegetables and the effect of decomposition on the reduction of PODS phytotoxicity. Raw and decomposed PODS was applied to sandy tailing soil at the levels of 0, 1, 3, 6, 9, 15 and 21 % (w/w) and planted with tomato and spinach seedlings. Samples of raw PODS were incubated at 30'C for 1, 2, 3, 4, 6 and 8 weeks and the aqueous extract of each sample was bioassayed for growth inhibition of tomato radicles. Results from the glasshouse experiment showed that growth of tomato and spinach was strongly affected by the type (raw or decomposed) and amount of PODS applied. Growth of both plants was inhibited by application of >1%raw PODS. In contrast, application of 1- 21 % decomposed PODS increased plant growth, with maximum dry matter production at 6% level. At this level, shoot dry weights of tomato and spinach increased 7 and 178 times, respectively, while root dry weights increased 1.6 and 62 times, respectively, compared to plants in raw PODS. Soil N, P and K contents, pH and electrical conductivity also increased with increase in PODS levels. The incubation study showed that the phytotoxicity of raw PODS was reduced when PODS was decomposed for > 4 weeks.